The municipal Charter of Lublin of 1317. The seven hundredth anniversary of granting the municipal charter - Nikołajew, Jerzy (The Opole Studies in Administration and Law, 2019)
The Municipal Charter granted to Lublin in 1317 by Prince Władysław the Short was the then state power’s acknowledgement for the urban aspirations of the town which at that time gained the status of a metropolis of the eastern Poland. The powers of the mayor and the burgesses of Lublin were the re-enactment of the provisions contained in other charters of that period, which resulted from the adoption of the German town law. The founding document of Lublin failed to include certain specific provisions (e.g. the right to timber, the right of storage, the right of fair days). However, other privileges concerning common town-related decisions (e.g. the right to land, own judiciary, share in income from rents) were typical of charters granted under the Magdeburg Law.